Recent Advances in Transition-Metal-Catalyzed [2+2+2]-Cyclo(co)trimerization Reactions - Broere, Daniël L. J.; Ruijter, Eelco (Synthesis, 2012)
Transition-metal-catalyzed [2+2+2] cyclo(co)trimerization reactions are a powerful methodology to synthesize various complex multi-substituted (poly)cyclic molecules in a single step with optimal atom efficiency. Ever since the discovery, the reaction has been plagued by issues concerning regio- and chemoselectivity. Over the last decades many advances have been made to overcome these issues by, for example, employing regio-directing groups or tethering the reaction partners together in an intramolecular approach. These solutions, however, have certain limitations. Nowadays, it is also possible to synthesize chiral molecules by performing an asymmetric transition-metal-catalyzed [2+2+2]-cyclo(co)trimerization reaction. This review focuses on the recent advances in mechanistic insight, solving the regioselectivity issue, synthesis of chiral molecules and alternative approaches for the synthesis of substituted benzenes, pyridines and 2-pyridones. In addition, recent applications in areas such as total synthesis of natural products are also described, demonstrating that the transition-metal-catalyzed [2+2+2]-cyclo(co)trimerization reaction is a powerful tool and a welcome addition to the chemist’s ‘synthetic toolbox’. 1 Introduction2 Synthesis of Benzene Derivatives2.1 Mechanistic Insight2.2 Regioselectivity2.3 Synthesis of Chiral Systems2.4 Other [2+2+2] Approaches2.5 Synthesis of (Iso)quinolines3 Synthesis of Pyridine Derivatives3.1 Mechanistic Insight3.2 Regioselectivity3.3 Synthesis of Chiral Systems4 Synthesis of Pyridone Derivatives 4.1 Mechanistic Insight4.2 Regioselectivity4.3 Synthesis of Chiral Systems 5 Applications 6 Future Directions7 Conclusion
Keywords: alkynes; cyclization; cycloaddition; homogeneous catalysis; transition metals